Method for preparing catalyst-assisted polypyrrole nanoparticles decorated graphene film for high-performance supercapacitor - Lim, Hong Ngee; Lim, Yee Seng; Huang, Nay Ming (2013)
A method for preparing polypyrrole and graphene nanocomposite films includes the steps of: providing a graphite source and oxidizing the graphite source to form graphite oxide solution, washing the graphite oxide solution for thickening the graphite oxide solution, creating a dispersion of the graphite oxide solution in a liquid, thickening the graphite oxide solution to form a graphite oxide gel, introducing at least one reagent into an one-compartment cell, providing a deposition solution and dipping it in the graphite oxide gel, stirring the deposition solution for a particular time period, reacting the at least one reagent to form polypyrrole within the deposition solution, providing a substrate, and applying an electric field across at least a portion of the deposition solution dipped in the graphite oxide gel for depositing at least one portion of graphene from the graphite oxide gel and the deposition solution on the substrate to form polypyrrole and graphene nanocomposite films.